Identification of Single Nucleotide Variation (SNV) -1082 A/G Gen Interleukin 10 (IL-10) in Tuberculosis Patients Using ARMS-PCR Method: Identifikasi Single Nucleotide Variation (SNV) -1082 A/G (rs1800896) Gen Interleukin 10 (IL-10) pada Penderita Tuberkulosis Menggunakan Metode ARMS-PCR - Dewi Saroh; Aninda Hana (Universitas Muhammadiyah Purwokerto, 2026)
Tuberculosis (TB) is a significant global health problem and remains one of the leading causes of high morbidity and mortality worldwide. Genetic variation in the interleukin-10 (IL-10) gene, particularly SNV -1082 A/G (rs1800896), plays an important role in regulating the immune response to Mycobacterium tuberculosis. This study aimed to determine the distribution of genotypes and alleles of SNV -1082 A/G (rs1800896) in the IL-10 gene among tuberculosis patients and healthy individuals. A descriptive study was conducted using a total of 12 blood samples (6 active TB patients from Puskesmas Delanggu Klaten and 6 healthy individuals as controls). Identification of the SNV was performed using the ARMS-PCR method, followed by electrophoresis and DNA band analysis. The results showed that the A/A genotype was more frequently observed in TB patients, while the A/G genotype was more frequent in healthy individuals. The A allele was more dominant in TB patients, whereas the G allele was more common in the healthy group. These findings provide a preliminary overview of genotype and allele distribution in a limited population. However, the very small sample size represents a major limitation of this study, and therefore the findings should only be considered preliminary and cannot be generalized. Further studies with larger sample sizes are required to confirm these results. ABSTRAK (Bahasa Indonesia) Tuberkulosis (TB) merupakan masalah kesehatan global yang signifikan dan masih menjadi penyebab morbiditas dan mortalitas tinggi. Variasi genetik pada gen interleukin-10 (IL-10), khususnya SNV -1082 A/G (rs1800896), berperan penting dalam regulasi respon imun terhadap Mycobacterium tuberculosis. Penelitian ini bertujuan untuk mengetahui distribusi genotipe dan alel SNV -1082 A/G (rs1800896) gen IL-10 pada pasien tuberkulosis dan individu sehat. Penelitian dilakukan secara deskriptif dengan total 12 sampel darah (6 pasien TB aktif dari Puskesmas Delanggu Klaten dan 6 individu sehat sebagai kontrol). Identifikasi SNV dilakukan menggunakan metode ARMS-PCR, dilanjutkan dengan elektroforesis dan analisis pita DNA. Hasil menunjukkan bahwa genotipe A/A lebih banyak ditemukan pada pasien TB, sedangkan genotipe A/G lebih banyak pada individu sehat. Alel A lebih dominan pada pasien TB, sementara alel G lebih banyak pada kelompok sehat. Hasil ini memberikan gambaran awal distribusi genotipe dan alel pada populasi terbatas. Namun, jumlah sampel yang sangat kecil menjadi keterbatasan utama penelitian ini, sehingga temuan hanya dapat dianggap sebagai data awal (preliminary) dan belum dapat digeneralisasi. Penelitian lanjutan dengan jumlah sampel lebih besar sangat diperlukan untuk mengonfirmasi hasil ini